Taking stock of the functioning of the EU fiscal rules and options for reform - Christophe Kamps; Nadine Leiner-Killinger (European Central Bank (ECB), 2019)
This paper reviews developments in fiscal rules in the European Union (EU) from the entering into force of the Treaty on European Union (the 'Maastricht Treaty'), which laid the foundations for the euro, until today. It seems safe to say that fiscal positions in the EU and the euro area are now more favourable than they would have been in the absence of the Maastricht Treaty and the Stability and Growth Pact (SGP). However, the aggregate picture masks significant cross-country heterogeneity, with less progress where it would be needed most. Furthermore, the design of the rules has not always followed economic logic and has often been the product of political constraints, giving rise to some flaws in the framework from the outset. Repeated attempts to adjust the fiscal framework to a multitude of circumstances over the past 25 years have made it overly complex and incoherent. The paper concludes that, in its current shape, the SGP is an insufficient disciplining device in economic good times, with the consequence that there are no fiscal buffers, particularly in high-debt countries, to support growth in economic troughs. This, together with the absence of a central fiscal stabilisation instrument, puts the burden of stabilisation mostly on the single monetary policy. The paper also reviews reform options on how to render the fiscal framework more effective in bringing about sounder public finances and avoiding the procyclicality observed over the past two decades.
Keywords: H11; H50; H6; 330; Economic and Monetary Union (EMU); fiscal rules; Stability and Growth Pact (SGP)